2011
DOI: 10.1038/ejhg.2011.201
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary conserved longevity genes and human cognitive abilities in elderly cohorts

Abstract: Genetic influences have an important role in the ageing process. The genetic factors that influence success in bodily ageing may also contribute to the successful ageing of cognitive abilities. A comparative genomics approach found longevity genes conserved between yeast Saccharomyces cerevisiae and nematode Caenorhabditis elegans. We hypothesised that these longevity genes influence variance in cognitive ability and age-related cognitive decline in humans. Here, we investigated six of these genes that have hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…In addition to the 125 genes considered above, many of the genes identified as associated with domestication by only one of the four methods are potentially interesting and worthy of further research. These genes include synaptojanin 2 (SYNJ2), which has been detected with PAML [phylogenetic analysis by maximum likelihood; false discovery rate (FDR) = 5%] and represents a longevity gene candidate associated with variation in levels of agreeableness and cognitive abilities (60,61). Such changes could have been instrumental in the development of tameness and increased social interactions with humans.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the 125 genes considered above, many of the genes identified as associated with domestication by only one of the four methods are potentially interesting and worthy of further research. These genes include synaptojanin 2 (SYNJ2), which has been detected with PAML [phylogenetic analysis by maximum likelihood; false discovery rate (FDR) = 5%] and represents a longevity gene candidate associated with variation in levels of agreeableness and cognitive abilities (60,61). Such changes could have been instrumental in the development of tameness and increased social interactions with humans.…”
Section: Resultsmentioning
confidence: 99%
“…It is differentially expressed in hippocampal sub-regions of the marmoset primate [47] and shows decreased expression in the human temporal cortex in persons with major depressive disorder [48]. SYNJ2 has been associated with cognitive abilities in two independent elderly cohorts [49]. Finally, haploinsufficiency of SYNJ2 due to a microdeletion on 6q is associated with a syndrome that presents with microencephaly, developmental delay and agenesis of the corpus callosum [50].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, deletions of other genes encoding mitoproteases, such as Afg3l2, Clpp and Parl, cause severe defects in mice, such as axonal degeneration, multisystem disorder and cachexia by general atrophy, respectively, which ultimately shorten their lifespan owing to impaired mitochondrial activities 41,106,117 . By contrast, another study suggested that single nucleotide polymorphisms (SNPs) in AGF3L2 are associated with longevity and enhanced cognitive abilities in elderly humans 118 .…”
Section: Mitochondrial Proteolysis and Ageingmentioning
confidence: 97%